(untitled) (World Bulletin of Management and Law, 2022)
This study aimed to identify the role of the audit committee and its impact on improving the quality of financial reports, as well as its impact on the efficiency and effectiveness of the audit and the quality of information in financial reports. To achieve this goal, studies related to both governance, the audit committee, and the quality of financial reports have been extrapolated, and the characteristics of the audit committee, how it is formed, and what is the quality of financial reports and ways to measure them have been extrapolated. One of the most important results was that there is a positive relationship between the independence of the committee, scientific qualification and financial experience, and the quality of financial reports. The study concluded with a set of recommendations, the most important of which is the need to pay attention to the characteristics that must be available in the audit committee and to preserve their independence